Chemical residuality in maize (Zea mays L.) fields irrigated with deep well water - Azpilcueta-Pérez, Ma. Elizabeth; Pedroza Sandoval, Aurelio; Trejo-Calzada, Ricardo; Sanchez-Cohen, Ignacio; Jacobo-Salcedo, María Del Rosario (Ecosistemas y Recursos Agropecuarios, 2018)
The aim was to conduct a residual analysis of the main cationic elements, heavy metals and arsenic in irrigated maize fodder production. Four soil and maize plant samplings were conducted in eight sites in April, May, June and July, 2014. Ca, Na, As, and Pb concentrations were higher in the soil. The As concentration was higher in June and July. La Purísima had a higher As concentration, while Bermejillo, La Galicia and La Rosita had a higher Ca concentration. K, Ca, Pb and Zn had higher concentrations in the maize plant, with Ca, Na and K having highervalues in July and Mg, Pb and Zn being higher in May and July. The content of Ca, Mg, Na and K did not dier among regions; arsenic was higher in Leon Guzmán and La Rosita.